Physical activity, leisure-time management, perceived barriers to physical activity and mental well-being among Turkish university students - Yunus Emre Kundakcı; Sultan Karaman; Medine Sıla Ateş (Discover Mental Health)
Abstract This study examined the relationship between physical activity (PA) level, free time management, mental well-being, and perceptions of barriers to PA among university students. A cross-sectional survey was conducted with 723 Turkish university students, which included four questionnaires to assess participants’ PA levels, conditions of mental well-being, free time management, and perceived barriers to PA. Multivariate linear regression was performed to identify factors associated with the participants’ PA level. The study found that 216 (29.9%) of participants were inactive, 325 (45%) were minimally active, and 182 (25.1%) were health-enhancing active. While 25.23% of males were inactive, 42.02% were minimally active, and 31.45% were health-enhancing active, these rates were 31.4, 45.98, and 22.62% for females, respectively. These findings highlight that 3/4 of university students have inadequate PA levels. Changes in barriers to PA (p < 0.001), free time management (p = 0.040), and mental well-being (p < 0.001) were associated with PA levels. According to the regression analysis, only increased barriers to PA was a significant predictor of PA (p < 0.001). Given the role of health science students in public health, this study could help policymakers develop new strategies to promote healthy living and address barriers to PA, such as students' free time and mental health.